Feynman and His Physics The Life and Science of an Extraordinary Man - Resag, Jörg (Springer Biographies,, 2018)
This book takes the reader on a journey through the life of Richard Feynman and describes, in non-technical terms, his revolutionary contributions to modern physics. Feynman was an unconventional thinker who always tried to get to the bottom of things. In doing so, he developed an intuitive view that made him one of the greatest teachers of physics. The author captures this development and explains it in the context of the zeitgeist of modern physics: What revolutionary ideas did Feynman have, what contribution did he make to the development of quantum mechanics and quantum field theory, how can Feynman's methods be understood? Be enchanted by this book and understand the physics of the genius whose 100th birthday was celebrated in 2018.